O debate sobre reformas e regulação e o caso da ANEEL - Cavalcante Junior, Jofre Castelo Branco (2002)
This work aims to verify to wich extent human resources flexibility in regulatory agencies in Brazil is consistent with regulatory independence, required in its tinnancial, technical and personnel dimensions. Regulatory independence provides protection against the negative effects of rent-seeking activities, vested interests and political use of regulatory agencies. The work describes the formation process of the national electricity sector regulatory agency, its labour legal regime, management board and restructuring process of the brazilian electricity industry. It concludes that pre-stablished term hiring and the attempt to modify labour regime sets to repeat bureaucratic disfunctions that has typically characterized brazilian public sector since the thirties.